(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Ralph Waldo Emerson used the term Over-Soul to denote the relationship between individual soul and the universal soul. Emerson’s extensive reading of both Eastern and Western philosophies has prompted him to articulate such a concept that adheres to the philosophical discourses of both the continents. Emerson’s concept of the Over-Soul denotes inseparable, impersonal and eternal essence fundamental to human consciousness, integrity and nature. The concept has a universal appeal as scholars have examined the notion from the perspective of different schools of philosophy spanning across the globe. This universal approach of the notion poses Emerson at the centre of the Eastern and Western metaphysical discourse. Over-Soul resounds with the Eastern concepts like Brahman, Non-dualism and Sunya (Void). It also echoes with the concept of Sunya (void) articulated by Bhima Bhoi, an Odia saint poet. Both these concepts, ‘Over-Soul’ and ‘Sunya’ share a common notion that is Brahman, the Vedic concept of the Ultimate Reality or the Supreme Being. This Supreme Being or Brahman pervades all existence. It is the source and destination of every being. In their writings both Emerson and Bhoi articulate that the individual self (the soul) is part of the cosmic self (the Over-Soul). To them, Brahman is not an intangible essence but an active consciousness that binds the “seer and the seen, the subject and the object” into one metaphysical reality.